2022
DOI: 10.1108/qmr-01-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual deterrents of the green consumer

Abstract: Purpose The purpose of this study is to better understand consumers’ overall perceptions of “being green” in an attempt to address the green attitude–behavior gap. Design/methodology/approach This study features a qualitative study that uses a projective technique to tap into consumers’ underlying perceptions of those who purchase green products. A follow-up, quantitative study tests the mediation effects of perceived judgment and self-congruity perceptions on the green attitude–behavior gap. Findings The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 87 publications
(133 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, studies suggesting self-congruency as a significant mediator between self-perception or attitude and behaviour also found support in the present study since it was confirmed that self-congruity with green food products partially mediated the relationship between green self-identity and sustainable food consumption behaviour. For example, McLelland et al (2022) reported that the relationship between attitude towards being green (which actually is very close to the notion of green self-identity) and green behaviours was mediated by self-congruity with "green consumer". They also found that self-congruity perceptions had a positive effect on green behavioural intention, as well as the direct positive effect of attitude on intentions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, studies suggesting self-congruency as a significant mediator between self-perception or attitude and behaviour also found support in the present study since it was confirmed that self-congruity with green food products partially mediated the relationship between green self-identity and sustainable food consumption behaviour. For example, McLelland et al (2022) reported that the relationship between attitude towards being green (which actually is very close to the notion of green self-identity) and green behaviours was mediated by self-congruity with "green consumer". They also found that self-congruity perceptions had a positive effect on green behavioural intention, as well as the direct positive effect of attitude on intentions.…”
Section: Discussionmentioning
confidence: 96%
“…Despite concern about sustainability and positive attitudes toward the environment, consumers may be unwilling to buy green products if they do not identify themselves with being green. According to McLelland et al (2022), when it comes to action, consumers may experience a variety of contrasting feelings that result in a lack of commitment to the green movement.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing research on green consumption, an attitude-intention gap remains for green products. Scholars must investigate this gap, which raises critical implications for environmental protection and the achievement of corporate sustainability goals (McLelland et al, 2022).…”
Section: Green Consumptionmentioning
confidence: 99%
“…Accordingly, a relatively novel way to understand why male and female consumers are sometimes differentially inclined to engage in green consumption, beyond established sex differences in certain personality traits, is to attribute these sex-specific patterns to the green-feminine stereotype (Borau et al, 2021;Brough et al, 2016;Felix et al, 2022;Huang et al, 2022). In other words, men may be more motivated than women to actively avoid green consumption to preserve a macho image (Bloodhart and Swim, 2020;McLelland et al, 2022;Rozin et al, 2012). Instead, they often opt for contrasting consumption choices that better communicate masculinity and hence prefer products that are unsustainable and wasteful, considering the link between such products and masculinity (Chan and Zlatevska, 2019;Gal and Wilkie, 2010;Griskevicius et al, 2007;Otterbring, 2018;Sundie et al, 2011).…”
Section: Sex Differences In Green Consumption Valuesmentioning
confidence: 99%
“…, 2022). In other words, men may be more motivated than women to actively avoid green consumption to preserve a macho image (Bloodhart and Swim, 2020; McLelland et al. , 2022; Rozin et al.…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%